PERTUMBUHAN DAN MORFOGENESIS KRISAN (Chrisanthemum Morifolium) KULO DENGAN EKSPLAN PUCUK DAN NODUS PADA MEDIA MS YANG DIBERI Benzil Amino Purin (BAP) - Lintong, Rieddel Toar Jullio; Mandang, Jeany Polii; Lengkong, Edy Fredy (AGRI-SOSIOEKONOMI, 2022)
This study aims to determine the effect of BAP on the growth and morphogenesis of Kulo Chrysanthemum with shoot and node explants by in vitro. This research was conducted from July to March 2021 at the Network Culture Laboratory of the Agriculture and Fisheries Service of Tomohon City. This study used a factorial completely randomized design (CRD), namely explant type factors consisting of shoot and node explants and BAP concentration factors were 0 mg/l, 0.5 mg/l, 1 mg/l, and 1.5 mg. /l so that there were 8 treatment combinations and each treatment was repeated 5 times resulting in 40 research units and one unit containing one explant. The results of this study showed that the interaction between explant type and BAP concentration had no significant effect on plantlet height, number of shoots, number of leaves, time of root formation (DAP), and time of shoot formation (DAP). Treatment The type of shoot and node explants had no significant effect on plantlet height, number of shoots, number of leaves, time of root formation (DAP) and time of shoot formation (DAP). The concentration of BAP had a significant effect on plantlet height, number of shoots, number of leaves, time of root formation (DAP) but had no significant effect on time of shoot formation (DAP).